State-of-the-Art Sensors Technology in Spain 2017 Volume 2 - Gonzalo Pajares Martinsanz (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
A comprehensive overview of sensors technology is provided in specific leading areas. Researchers, engineers and professionals on industries can find advanced technologies, devices, insights and solutions for a broad range of applications, including: • Piezoelectric power transducers • Multisensory for veins detection for robotic-based catheters insertion • Robot-sensor network cooperation for SLAM • Wind speed influences on RGB-D images in trees • Spectrophotometer for physiopathy detection in chickens • Radon gas and ionization detection • Vibrations measurements in robots • Architectures for multisensor intelligent robots • Ultrasound for tissue characterization • Active imaging model • Image-based for crack detection in tunnels • Wireless sensor nodes for energy harvesting, industrial monitoring, concrete cure • Vibroacoustic Impact on the Architectonic Heritage • Sensors motion capture in wearables • Torsional wave sensor • Model-based non-rigid tracking • Stair-Climbing Mobility • IoT-based people monitoring • Laser Speckle System • Odometric in an autonomous electric cart • New control paradigms • Concentric electrodes for ECG and intestinal exploration • Trusted virtual sensors • Thermo-Hygrometric measurements in archaeology • Intensive care unit • Multi-beam Lidar 3D scan • Hyperspectral Imaging in brain tumor • Crowdsensing in smart cities • Strain method to detect tires' loss • Optical force sensor • Portable sensor for substance concentration measurements • High-Frequency content in Human QRS complexes • Fusion of proximity sensors data • Electro-magnetic acoustic system • Computer vision on aerial robots for surface inspection • Dual-reflectarray antennas